Integrating conservation and economic objectives in MPA network planning: A case study from New Zealand. (June 2017) - Geange, Shane W.; Leathwick, John; Linwood, Megan; Curtis, Helen; Duffy, Clinton; Funnell, Greig; Cooper, Sean
Abstract: Several international agreements and conventions require nations to establish Marine Protected Area (MPA) networks as an approach to alleviating biodiversity declines; however, a common problem in planning MPA networks is how to balance conservation objectives against economic objectives. Here, using the distributions of 102 biodiversity features and 7 extractive uses we trial the systematic conservation planning software Zonation as a decision-support tool to facilitate progress towards New Zealand's commitment to establishing a representative network of MPAs while providing for economic development. Our results indicate that: (i) New Zealand's existing MPAs provide on average 70% less representation of the input biodiversity features than would be achieved by an MPA network of equivalent area designed from the outset using Zonation; (ii) small increases in the geographic extent of existing protection results in rapid increases in representation of the selected biodiversity features when systematic conservation planning software is used to inform expansion of existing protection; and (iii) the impacts on existing resource users of an expanded MPA system can be minimized by using Zonation to identify areas that increase biodiversity representation, while avoiding areas where existing uses may be incompatible with marine protection. These results demonstrate the utility of systematic conservation planning software as a decision-support tool within a broader social process for MPA network design and implementation. The iterative application of tools such as Zonation during participatory processes that balance alternative uses could potentially lead to more informed, efficient and socially enduring outcomes that enhance the ability to establish representative MPA networks. Highlights: We evaluated New Zealand's existing MPAs using the conservation software Zonation Existing MPAs are inefficient in protecting a representative range of biodiversity Small increases in the spatial extent of existing protection could result in rapid increases in biodiversity representation This could be achieved while minimizing impacts on existing resource users